2015
DOI: 10.5812/jjm.27896
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Rubella in Women Under 25 Years Old Attending Medical Centers in Ahvaz, Iran in 2013

Abstract: Background:Rubella is a mild viral infection affecting women of reproductive age, and the fetus in early pregnancy, leading to miscarriage, stillbirth and Congenital Rubella Syndrome.Objectives:The present study aimed to assess serum level of anti-rubella antibodies in women younger than 25 years attending medical centers in Ahvaz city.Patients and Methods:This descriptive cross-sectional study was conducted on 760 women younger than 25 years attending medical centers in Ahvaz. A sample of 3 mL of venous blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A hospital-based study in Iran to quantitatively assayed the anti-rubella IgG and found that 88.9% had immunity against rubella, while a tenth of the respondents had no immunity. 25 The level of rubella IgG in a country with rubella vaccination policy like Iran, is one way to measure the degree of protection or immunity the people have against rubella; and it is a way to measure the success or failure of the vaccination program as earlier stated.…”
Section: Discussionmentioning
confidence: 99%
“…A hospital-based study in Iran to quantitatively assayed the anti-rubella IgG and found that 88.9% had immunity against rubella, while a tenth of the respondents had no immunity. 25 The level of rubella IgG in a country with rubella vaccination policy like Iran, is one way to measure the degree of protection or immunity the people have against rubella; and it is a way to measure the success or failure of the vaccination program as earlier stated.…”
Section: Discussionmentioning
confidence: 99%
“…If the infection happens in early pregnancy, the fetus will be at risk of complications in the form of spontaneous abortion, intrauterine growth retardation and congenital rubella syndrome (CRS). CRS is a congenital malformation of several organs in the fetus with many manifestations such as cataracts, deafness, cardiac defects, hepatosplenomegaly, low birth weight and skin rash at birth 2‐4 . The World Health Organization (WHO) reported that annually >100 000 infants are born with CRS worldwide 2,5 .…”
Section: Introductionmentioning
confidence: 99%
“…CRS is a congenital malformation of several organs in the fetus with many manifestations such as cataracts, deafness, cardiac defects, hepatosplenomegaly, low birth weight and skin rash at birth. [2][3][4] The World Health Organization (WHO) reported that annually >100 000 infants are born with CRS worldwide. 2,5 There is no available therapy for pregnant females or infants affected with rubella.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Iran, rubella seroprevalence ranged from about 89% among women below 25 y of age to 85% among children under-five, dropping to 81.4% in 11-15 y olds with the highest figures (98.8%) among 21-25 y olds. 18 Another Iranian study among pregnant women found that 96% of participants were immune to rubella. 14 In Germany, 87.6% of children below 17 yof age were immune to rubella 12 with the age group of 3 to 6 y olds having the highest proportion of immune individuals.…”
Section: Introductionmentioning
confidence: 99%